Electrical Artery Model for the Evaluation of Non-Linear Compliance - Kupciunas, I.; Kopustinskas, A. (Elektronika ir Elektrotechnika, 2012)
Arterial compliance is one of the major indices characterizing arterial stiffness. Electrical analogy artery model, which incorporates elements, characterizing all four main effects of the blood flow, and enables evaluation of pressure-dependent compliance using non-invasive techniques, was proposed in this study. Assumption that, blood inertance together with non-linear compliance enables more accurate representation and provides quantitatively and qualitatively improved diagnostic information, was validated in initial experimental in vivo study of human carotid artery. Mean value of inadequancy for CP - 9,69 % was obtained comparing proposed four and two element models. Ill. 5, bibl. 6, tabl. 3 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1061